2016
DOI: 10.2217/fon-2016-0084
|View full text |Cite
|
Sign up to set email alerts
|

Obinutuzumab For The Treatment Of Indolent Lymphoma

Abstract: Obinutuzumab is a humanized, type II anti-CD20 monoclonal antibody designed for strong induction of direct cell death and antibody-dependent cell-mediated cytotoxicity. The Phase III GADOLIN trial tested the clinical efficacy of obinutuzumab plus bendamustine followed by obinutuzumab monotherapy in rituximab-refractory indolent non-Hodgkin lymphoma versus treatment with bendamustine alone. It demonstrated significantly longer progression-free survival for the obinutuzumab-containing regimen in this difficult t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 62 publications
(72 reference statements)
0
2
0
Order By: Relevance
“…Overall, ZO toxicity profile is consistent with the known and tolerable safety profiles of each drug, with no unexpected additional concerns. 33,34 Bleeding incidence was lower than that observed in other indications, with no major hemorrhage attributed solely to ZO therapy. Incidences of atrial fibrillation and hypertension were low with ZO and similar to those reported with O alone.…”
Section: Discussionmentioning
confidence: 59%
“…Overall, ZO toxicity profile is consistent with the known and tolerable safety profiles of each drug, with no unexpected additional concerns. 33,34 Bleeding incidence was lower than that observed in other indications, with no major hemorrhage attributed solely to ZO therapy. Incidences of atrial fibrillation and hypertension were low with ZO and similar to those reported with O alone.…”
Section: Discussionmentioning
confidence: 59%
“…Our case clearly demonstrates that association between obinutuzumab and PML exists and undoubtedly confirms the safety precaution from the drug-label. Obinutuzumab is more potent in terms of B-cell depletion than rituximab [3] and it is expected to be increasingly used in the treatment of CLL and indolent B-cell lymphomas. Our case underlies the fact that the current incidence of PML during obinutuzumab treatment is unknown and further investigations regarding exposure to obinutuzumab, as well as number of incident cases associated with exposure are needed to clearly establish safety of such potent therapy.…”
Section: Dear Editormentioning
confidence: 99%